Discourse on Social Exclusion and Inclusion in Nepal: A Review - Shrestha, Bishal (Dristikon: A Multidisciplinary Journal, 2022)
The discourse of social exclusion and inclusion is debatable issue in contemporary Nepali society. The issue of social exclusion should be addressed by adopting the process of social inclusion in several sectors of Nepali society which helps to establish society with equality. The article Social Exclusion and Inclusion tries to address the issue raised in the discourse of social inclusion. Similarly, it tries to explore the issue of social exclusion and inclusion from new line. Article is based on the review of the several articles published addressing the issue of social exclusion and inclusion. In introduction, I have mentioned the context and origin of social exclusion and inclusion debate. Different views of various renowned scholars on Social Exclusion and Inclusion have been mentioned. In Nepalese context, political movement and academic effort of social exclusion and inclusion have been discussed. The achievement that excluded group got in the Constitution and other Acts from the political and other inclusion movement have been disclosed here. In Nepal, there are three types of notions/domains: Inclusive based on Caste Ethnicity, Economy Prosperity and Meritocracy. I critically support the Inclusive based on Caste Ethnicity Movement.